Gender interfaces and women's empowerment in Korfball: A descriptive review - Laudares Silva, Renata [UNESP]; Schwartz, Gisele Maria [UNESP] (FapUNIFESP (SciELO), 2020)
Based on the perspective of gender equality in sport, this study investigated the production of knowledge about gender interfaces and women’s empowerment in Korfball. The results indicate the predominance of studies about gender equality in highperformance sports, and in physical education classes. However, no articles were found directly related to gender interfaces and women’s empowerment in Korfball. It is concluded that there is an urgent need for production of knowledge about this theme, to minimize this gap.
Interfaces de gênero e empoderamento da mulher no Corfebol: Uma revisão descritiva*
Keywords: Gender Identity; Korfball; Power (Psychology); Sport